The Impact of Mathematics Anxiety and Self-Efficacy Towards Prospective Mathematics Teachers’ Performance - Yanti, Liza Puspita; Suryanti, Sri; Siripala, Wannaporn (Jurnal Pendidikan MIPA, 2025)
Mathematics anxiety is one of the serious emotional aspects that may impair the academic performance and interest in mathematics in students. This paper presents a study of the correlation between mathematics anxiety, mathematics self-efficacy, and mathematics performance among 150 future mathematics teachers in Indonesia, who were identified through purposive sampling of an undergraduate teacher education program. The Mathematics Anxiety Rating Scale- Revised (MARS-R), Mathematics Self-Efficacy Scale- Revised (MSES-R), and a self-developed Mathematics Achievement Test (MAT) were used to collect data. Pearson correlation and multiple regression were used to address the relationship and the predictive attributes of these variables. Descriptive analysis indicated that participants had moderately high mathematics anxiety (M = 82.4, SD = 15.2), moderately high self-efficacy (M = 72.8, SD = 12.5), and good performance (M = 78.3, SD = 10.7). Pearson correlation analysis revealed a negative correlation between mathematics anxiety and performance (r = -0.62, p < 0.001). In contrast, self-efficacy had a positive correlation with performance (r = 0.6). Regression analysis showed that both anxiety (β = -0.45, p < 0.001) and self-efficacy (β = 0.49, p < 0.001) were significant predictors. The results of the multiple regressions showed that the model was significant, F(2, 147) = 68.24, p < 0.001, and accounted for 55.7% of the variance in performance (R² = 0.557). Anxiety (B =-0.45) and self-efficacy (B =0.49) were both significant predictors of performance (B = -0.45, t = -7.62 p = 0.001) and self-efficacy (B = 0.49, t = 8.15, p = 0.001) turned out to be the stronger predictors. The practical implications of these findings are most significant, as strategies aimed at diminishing mathematics anxiety and enhancing self-efficacy should be the primary focus of mathematics teacher education programs, as these aspects directly relate to the competency and confidence of future teachers in teaching mathematics.   Keywords: mathematics anxiety, self-efficacy, academic performance, future mathematics teachers, mathematical confidence, mathematical teacher education.